Pengalaman Perawat Dalam Penanganan Pasien Amuk Dengan Restrain Extremitas Di Rumah Sakit Jiwa Arif Zainudin Surakarta - Faradhila, Fajar; , Arum Pratiwi, S.Kp., M.Kes (2017)
Background: Patient with violent behavior is a form of aggressive behavior, Aggressive behavior is a form of behavior that aims to injure others physically and psychologically. Patients need more specific treatment with violence compared to the patients with calmer condition. The acute room and the emergency room are place where most patients handle a with extremitas restrain. To handle patients with medical personnel violent behavior especially psychiatry nursing staff has a important role one of them is with extremitas restrain. As a nurse must have different experience in dealing with violence patients with extremitas restrain. There are many challenges to be faced when dealing with an amateur patient with extremity restraints. The purpose of this study is to know the experience of nurses in the handling of violent behavior patients with extremitas restrain. Method: This research is a type of qualitative research using phenomenological approach. Participants amounted of 5 people who are acute space nurses and emergency room at Arif Zainudin psychiatric Hospital Surakarta. In the selection of participants are assisted by the head of space in accordance with the criteria of researchers and has reached the level of redundancy or data has been saturated plus participants no longer provide new information. The sample technique used is purposive sampling technique. Data were collected through in-depth interviews and nurse observations in the treatment of amok patients with extremity restraints. The results of the research: after the thematic analysis process, identified three themes, namely the stages in the nursing care of violent behavior patient with extremitas restrain, self-awareness of the nurse to the duties and responsibilities as a nurse, reception nurses in handling patients violent behavior with restrain extremities. Suggestions for further research may add factors related to the nurse's ability to carry out restrain in the patient violent behavior, so it is known what factors are related to the ability or performance of the mental nurse. Keywords: Patient with violent behavior, Restrain Extremitas, Experience nurse